Employment protection versus flexicurity: on technology adoption in unionised firms - Kjell Erik Lommerud; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyse how different labour market institutions - employment protection versus flexicurity - affect technology adoption in unionised firms. We consider both trade unions' incentives to oppose or endorse labour-saving technology, and firms' incentives to invest in such technology. We find that increased flexicurity interpreted as less employment protection and a higher reservation wage for workers - unambiguously increase firms' incentives for technology adoption, even when taking into account the response in unionised wage setting to such new technology. If we assume that unions have some direct influence over the technology to be adopted, a higher reservation wage also makes unions more willing to accept technological change. Less employment protection has the opposite effect, since this increases the downside (job losses) of labour-saving technology.
Keywords: J51; O33; 330; Technology adoption; trade unions; employment protection; flexicurity; Technologiewahl; Gewerkschaftlicher Organisationsgrad; Kündigungsschutz; Arbeitsmarktflexibilisierung; Flexicurity; Anspruchslohn; Endogener technischer Fortschritt; Arbeitsproduktivität; Theorie